2003
DOI: 10.1021/ac0206420
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Rapid Ferricyanide-Mediated Assay for Biochemical Oxygen Demand Using a Mixed Microbial Consortium

Abstract: Ferricyanide-mediated (FM) microbial reactions were used for the rapid determination of the biochemical oxygen demand (BOD) of a range of synthetic and real wastewater samples. Four single-species microbial seeds and a synthetically prepared microbial consortium were compared. In all cases, the microbial consortium exhibited a greater extent and rate of biodegradation compared to the individual microbial seeds. Markedly improved correlation to the standard BOD5 method was also noted for the microbial consortiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 28 publications
1
40
0
1
Order By: Relevance
“…Second, unlike oxygen, the reduced form of the mediator has an initial background concentration of zero, thereby increasing the accuracy when quantifying the amount of oxidised mediator converted to its reduced form. In recent studies, we demonstrated that the ferricyanide-mediated microbial oxidation of organic substrates by Eschericha coli in a 1-h MICREDOX ® incubation was equivalent to that achieved in the traditional BOD 5 test (60.5%) (Pasco et al, 2000;Morris et al, 2001;Catterall et al, 2003). A second application, again demonstrated with E. coli, confirmed the utility of this method for rapidly quantifying the effect of toxic substances on microbial catabolism .…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…Second, unlike oxygen, the reduced form of the mediator has an initial background concentration of zero, thereby increasing the accuracy when quantifying the amount of oxidised mediator converted to its reduced form. In recent studies, we demonstrated that the ferricyanide-mediated microbial oxidation of organic substrates by Eschericha coli in a 1-h MICREDOX ® incubation was equivalent to that achieved in the traditional BOD 5 test (60.5%) (Pasco et al, 2000;Morris et al, 2001;Catterall et al, 2003). A second application, again demonstrated with E. coli, confirmed the utility of this method for rapidly quantifying the effect of toxic substances on microbial catabolism .…”
Section: Introductionmentioning
confidence: 53%
“…In all reported cases, the decrease in dissolved oxygen forms the basis of the analytical signal. One consequence of oxygen limitation for microbial BOD sensors is the amount of organic material biodegraded in a short-time assay is small, representing only a very small fraction of the total biodegradable organic content Catterall et al, 2003). Mini-wastewater treatment plants, such as RODTOX ® , BIOX ® , BIOMONITOR ® and RACOD ® are designed to replicate the operation of a wastewater treatment plant, rather than the methodology of the BOD test.…”
Section: Introductionmentioning
confidence: 99%
“…Pseudomonas species are able to grow with cyanide as the sole nitrogen source and several enzyme activities of these bacterial strains were significantly higher than those observed with other nitrogen sources [34]. Also the bacterial cells exhibited a greater extent and rate of biodegradation in the presence of ferricyanide as the terminal electron acceptor compared to the individual cells [35].The purpose of this study is to investigate biodesulphurization ability of P. aeruginosa supported on polyethylene in the presence of potassium hexacyanoferrate(III) in thiophene biodegradation as an aromatic sulphur model compound of crude oil.…”
Section: Introductionmentioning
confidence: 88%
“…Ferricyanide (FC) acts as an efficient mediator for shuttling electrons between the redox centers of reduced bacterial enzymes and the electrode surface. 6 In the presence of FC as a mediator, electrons derived from the oxidation of organic substrates in aerobic catabolism are transferred to the FC ion which is reduced from ferricyanide to ferrocyanide, 7 as shown in Eq. (2.1).…”
Section: Ferricyanide-mediated Bod Sensormentioning
confidence: 99%